2022
DOI: 10.1108/heswbl-04-2021-0070
|View full text |Cite
|
Sign up to set email alerts
|

A proposed model to design MOOCs through the lens of addressing graduate skill gap

Abstract: PurposeThe purpose of this study is to understand the mediating role of psychological need and immersive experience on graduates' skill gaps on massive open online courses (MOOCs) adoption intention.Design/methodology/approachThe proposed research model is developed by combining two popular theoretical models, namely, the self-determination theory, network externalities theory along technology adoption theory. Data are collected from 318 respondents to test the model. Structural equation modeling (SEM) is appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 67 publications
1
17
0
Order By: Relevance
“…Prior studies have shown that socioeconomic variations like educational attainment and psychological aspects (eg, perceived fear to and perceived severity of the diseases) are significantly associated with engagement in protective behaviours. [46][47][48][49] Therefore, learners are showing their protective behaviours 50 by attaining online courses. According to Shah, 51 Over 2800 courses, 19 online degrees, 360 micro certificates, and other offerings were released by various platforms.…”
Section: Perceived Fear and Moocsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have shown that socioeconomic variations like educational attainment and psychological aspects (eg, perceived fear to and perceived severity of the diseases) are significantly associated with engagement in protective behaviours. [46][47][48][49] Therefore, learners are showing their protective behaviours 50 by attaining online courses. According to Shah, 51 Over 2800 courses, 19 online degrees, 360 micro certificates, and other offerings were released by various platforms.…”
Section: Perceived Fear and Moocsmentioning
confidence: 99%
“…This categorical service fulfils substantial learning needs of the students that derive from one’s motivation level. 7 , 8 In particular, a recent study posited that the majority of the students have strong determination to learn new skills, ideas, and subjects that will help them to become experts in their field of study and profession. 9 However, the inability of MOOC providers to concurrently deliver courses with a wide range of subjects worries some other experts.…”
Section: Introductionmentioning
confidence: 99%
“…Blanco et al (2016) stated that a number of students and employers engaged in MOOCs to bridge employability gaps. Hossain et al (2022) found that awareness of psychological needs and opportunities for immersive experiences mediated the impact of skill gaps and social interaction on graduates' MOOC acceptance intention. Hence, it is critical to develop MOOC courses that increase learners' employability skills.…”
Section: Conclusion Implications and Future Directionsmentioning
confidence: 98%
“…Hossain et al (2020) found that learners' satisfaction, combined with cognitive need and attitude, were core conditions that enhanced continuance intention. Hossain et al (2022) found that psychological needs and immersive experiences mediated graduates' skill gap as well as their willingness to enroll in MOOCs. Finally, Padilha et al (2021) assessed MOOCs as an educational resource to enhance self-management intervention skills, and revealed that students were interested in participating in future MOOCs for their utilitarian value.…”
Section: Moocsmentioning
confidence: 99%
See 1 more Smart Citation